2015
DOI: 10.1002/anie.201507352
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Corrosion Triggered Spontaneous Generation of H2O2 on Oxidized Titanium for Promoting Angiogenesis

Abstract: Although the use of reactive oxygen species (ROS) has been extensively studied, current systems employ external stimuli such as light or electrical energy to produce ROS, which limits their practical usage. In this report, biocompatible metals were used to construct a novel electrochemical system that can spontaneously generate H2O2 without any external light or voltage. The corrosion of Mg transfers electrons to Au-decorated oxidized Ti in an energetically favorable process, and the spontaneous generation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Pro-angiogenic activity of Mg is regarded as a further added value for its usability in bone tissue engineering. Indeed, Mg can promote angiogenesis through enhancing the production of reactive oxygen species as well as through upregulating VEGF expressions in human endothelial cells [ 33 ]. Furthermore, it has been demonstrated that this element may increase new blood vessel formation, leading to improved bone reconstruction in vivo [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pro-angiogenic activity of Mg is regarded as a further added value for its usability in bone tissue engineering. Indeed, Mg can promote angiogenesis through enhancing the production of reactive oxygen species as well as through upregulating VEGF expressions in human endothelial cells [ 33 ]. Furthermore, it has been demonstrated that this element may increase new blood vessel formation, leading to improved bone reconstruction in vivo [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, electrons on conduction band (CB) of ZnO are able to generate superoxide ( • O 2 − ) . It is known that certain metal can donate electrons to metal oxide semiconductors by a self‐corrosive process . Therefore, it is proposed that electrons are donated from Zn to ZnO (CB) via interface effect and reduce oxygen molecules to superoxides in water.…”
mentioning
confidence: 99%
“…By repeating the chronoamperometry experiments in solutions purged with N 2 , a common approach for reducing O 2 concentration, [46] no significant differences on magnetically induced current increase at 1 T were observed as compared to the normal solution preparation (Figure 4 f). These results indicate negligible effects of superoxide on magnetically induced current increases at the recessed electrode, potentially due to the extremely fast spin relaxation of the superoxide (within a nanosecond) even if a [FMNH .…”
Section: Resultsmentioning
confidence: 97%